Using Aqueous Kaolinite Suspension as a Medium for Removing Phosphate from Water - Susmita Sen Gupta; Krishna G. Bhattacharyya (Adsorption Science & Technology)
Phosphates enter into water bodies mainly from non-point sources such as agriculture fields, which promote algal growth and cause eutrophication in lakes, wetlands, etc. Therefore, it is important to identify methods to reduce the level of phosphates in water bodies. In this work, we used kaolinite and its calcined and acid-activated forms as adsorbents for removing phosphate from an aqueous medium under different conditions of pH, concentration, amount of adsorbent, time and temperature. Our results showed that weakly acidic pH (∼5.0) favoured the adsorption of phosphates, which attained equilibrium within 180 min. The interactions followed second-order kinetics. Our data fitted well with linear isotherm models. A part of the phosphate interacts chemically with kaolinite, while some amount may be weakly held. Experiments at 303, 313, 323 and 333 K showed that the interactions are exothermic, with decreasing entropy and Gibbs' energy. We found that acid-activated kaolinite had the highest adsorption capacity for phosphate.